Genetic structure of three Landrace swine herds in Paraná, São Paulo and Minas Gerais states of Brazil - Saralegui, Walter H.; Irgang, Renato (Pesquisa Agropecuaria Brasileira, 2014)
The breed structure of Landrace Swine herds in Paraná (PR), São Paulo (SP) and Minas Gerais (MG) states of Brazil, were analysed by pedigree sampling methods. (II) From 1960, 1966, and 1973, until 1977, 9,544 pigs in PR, 16.226 pigs in SP and 3,933 pigs in MG, were registered, respectively. The registrations mean by year were 8.2%, 13.9% and 3.3% with relation to Landrace of Brazil, and the effective numbers (Ne) corresponded to 497, 445 and 87 for Paraná, São Paulo and Minas Gerais, respectively. (III) The most important herds, considering their genetic contribution, besides the "herds in the foreing countries" and the "imported boars" were "Sadia" and "Paumar" (PR). "Paineira" and "Baroneza" (SP) and "Agroceres" (MG). (III) The boars with a breed relationship over 3%, were: one (PR), three (SP) and 18 (MG). (VI) The total inbreeding by generation, from the first registration until 1977, were 0.05% (PR), 0.16% (SP) and 0.51% (MG). (V) The generation length averages were 25.5 months (PR), 23.3 months (SP) and 24.7 months (MG). (VI) The average replacement rates of boars from the same Elite Herd, were 26.2%, 52.5% and 77.3% for Paraná, São Paulo and Minas Gerais, respectively.